The Solvability and Optimal Controls for Some Fractional Impulsive Equation with Finite Delay - Liu, Xianghu; Li, Yanfang (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper is concerned with the existence and uniqueness of mild solution of some fractional impulsive equations withfinite delay. Firstly,we introduce the fractional calculus,Gronwall inequality, leray-schauder’sfixed point theorem,Secondly with the help of them, the sufficient condition for the existence and uniqueness of solutions is presented. Finally we give an example to illustrate our main results.